Advising women with diabetes in pregnancy to express breastmilk in late pregnancy (Diabetes and Antenatal Milk Expressing [DAME]): a multicentre, unblinded, randomised controlled trial - Forster, Della A; Moorhead, Anita M; Jacobs, Susan E; Davis, Peter G; Walker, Susan P; McEgan, Kerri M; Opie, Gillian F; Donath, Susan M; Gold, Lisa; McNamara, Catharine; Aylward, Amanda; East, Christine; et al. (The Lancet (British edition), 2017)
Infants of women with diabetes in pregnancy are at increased risk of hypoglycaemia, admission to a neonatal intensive care unit (NICU), and not being exclusively breastfed. Many clinicians encourage women with diabetes in pregnancy to express and store breastmilk in late pregnancy, yet no evidence exists for this practice. We aimed to determine the safety and efficacy of antenatal expressing in women with diabetes in pregnancy. We did a multicentre, two-group, unblinded, randomised controlled trial in six hospitals in Victoria, Australia. We recruited women with pre-existing or gestational diabetes in a singleton pregnancy from 34 to 37 weeks' gestation and randomly assigned them (1:1) to either expressing breastmilk twice per day from 36 weeks' gestation (antenatal expressing) or standard care (usual midwifery and obstetric care, supplemented by support from a diabetes educator). Randomisation was done with a computerised random number generator in blocks of size two and four, and was stratified by site, parity, and diabetes type. Investigators were masked to block size but masking of caregivers was not possible. The primary outcome was the proportion of infants admitted to the NICU. We did the analyses by intention to treat; the data were obtained and analysed masked to group allocation. This trial is registered with the Australian New Zealand Clinical Trials Registry, number ACTRN12611000217909. Between June 6, 2011, and Oct 29, 2015, we recruited and randomly assigned 635 women: 319 to antenatal expressing and 316 to standard care. Three were not included in the primary analysis (one withdrawal from the standard care group, and one post-randomisation exclusion and one withdrawal from the antenatal expressing group). The proportion of infants admitted to the NICU did not differ between groups (46 [15%] of 317 assigned to antenatal expressing vs 44 [14%] of 315 assigned to standard care; adjusted relative risk 1·06, 95% CI 0·66 to 1·46). In the antenatal expressing group, the most common serious adverse event for infants was admission to the NICU for respiratory support (for three [<1%] of 317. In the standard care group, the most common serious adverse event for infants was moderate to severe encephalopathy with or without seizures (for three [<1%] of 315). There is no harm in advising women with diabetes in pregnancy at low risk of complications to express breastmilk from 36 weeks' gestation. Australian National Health and Medical Research Council.